A Joint Interactive Storybook Intervention Program for Preschool and Kindergarten Children. Issue 3 (3rd April 2017) - Vaknin-Nusbaum, Vered; Nevo, Einat
Abstract : The effectiveness of a joint interactive storybook reading program delivered by class teachers to develop literacy skills is examined in Hebrew-speaking preschool and kindergarten children. Post-intervention, both groups achieved significantly higher gains in language and print concept skills than age-matched comparison groups that did not have the intervention. However, motivation to read improved significantly more in the experimental group than the comparison group in kindergarteners. Results suggest that intervention program using stories and embedded activities can enhance language and print concepts in young children. Also, motivation to read should be part of every intervention program aimed at enhancing literacy skills.